Water Quality 2017
DOI: 10.5772/65744
|View full text |Cite
|
Sign up to set email alerts
|

Metals Toxic Effects in Aquatic Ecosystems: Modulators of Water Quality

Abstract: The topic of this work was based on the assessment of aquatic systems quality related to the persistent metal pollution. The use of aquatic organisms as bioindicators of metal pollution allowed the obtaining of valuable information about the acute and chronic toxicity on common Romanian aquatic species and the estimation of the environment quality. Laboratory toxicity results showed that Cd, "s, Cu, Zn, Pb, Ni, Zr, and Ti have toxic to very toxic efects on Cyprinus carpio, and this observation could raise conc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
53
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 74 publications
(62 citation statements)
references
References 52 publications
0
53
0
1
Order By: Relevance
“…The single species toxicity tests were appropriate for analyzing toxicological effects on individual characteristics of species such as mortality or growth, but with limited significance for the consequences on the natural ecosystem. Before 2008, our laboratory performed LC50 individual species tests using fresh water bio indicators such as Cyprinus carpio and Daphnia magna to evaluate the acute or chronic toxicities of various chemicals (pesticides, metals or other inorganic or organic compounds) [11,29]. Currently, this tests are frequently request by producers or control authorities for chemical products authorization (such as biocide, industrial products or industrial wastes) or environmental samples toxicity control.…”
Section: Results and Discussion Aquatic Toxicity -Mono-species Expermentioning
confidence: 99%
See 1 more Smart Citation
“…The single species toxicity tests were appropriate for analyzing toxicological effects on individual characteristics of species such as mortality or growth, but with limited significance for the consequences on the natural ecosystem. Before 2008, our laboratory performed LC50 individual species tests using fresh water bio indicators such as Cyprinus carpio and Daphnia magna to evaluate the acute or chronic toxicities of various chemicals (pesticides, metals or other inorganic or organic compounds) [11,29]. Currently, this tests are frequently request by producers or control authorities for chemical products authorization (such as biocide, industrial products or industrial wastes) or environmental samples toxicity control.…”
Section: Results and Discussion Aquatic Toxicity -Mono-species Expermentioning
confidence: 99%
“…Thereby, risk characterization researches were initiated for some hazardous chemicals (4chloroaniline, 1-chloro-4-nitrobenzene and 4chloro-2-nitrotoluene), pesticides (azinphos-methyl and bentazone), pharmaceuticals (diclophenac, acetaminophen, ketoprophen, indomethacin, naproxen, ibuprophen, carbamazepine, caffeine, ciprofloxacine and trimethoprim), surfactants (benzenthonium chloride and cocamidopropyl betaine) and heavy metals. The studies showed the risk level of each chemical compound base on field data concentration respectively Romanian surface waters (Danube River, Danube Delta, Arges River, Mures River, Ciorogarla River and Ghimbasel stream) comparatively with other international rivers [11,16,29]. The results showed different levels of risk in accordance to detected environmental concentration, to acute and chronic toxicities and the environmental compartment (water or sediment).…”
Section: Fig 6 Chemical Aquatic Risk Assessmentmentioning
confidence: 95%
“…A greater difference of bioaccumulative metals impact (Ni and Zn) at S7 compared to S8 was observed. The study of metal bioaccumulation capacity in the mollusks shell from Danube Delta aquatic system underlined that metals involved in metabolic processes (such as Fe, Mn, Zn, Cu, and Mg) had a greater storage capacity than the toxic ones (such as Pb and Cd) [12].…”
Section: Methodology For Assessing the Metals Bioaccumulation In Bentmentioning
confidence: 99%
“…The bioaccumulation of numerous metals (such as: As, Se, Sb, Cd, Cr, Cu, Co, Fe, Mn, Mg, Ni, Pb and Zn) was quantified from two bivales species and one gasteropod species collected during summer and autumn 2013 from S7 and S8. The applied methodology was detailed in Gheorghe et al (2017)[12]. Benthic invertebrates as biological vectors for pathogens.…”
mentioning
confidence: 99%
“…The toxic metals are the most frequently detected pollutants in the aquatic environment, and their effects identification are essential to protect the ecosystems integrity as well as human health (Gheorghe, Stoica, Vasile, Nita-Lazar, Stanescu, & Lucaciu, 2017). Copper (Cu) is considered as the one of the most toxic metals to aquatic organisms.…”
Section: Introductionmentioning
confidence: 99%